MATERIAL OPTIMIZATION AND SELECTION FOR THE DESIGN OF SHELL AND TUBE HEAT EXCHANGER - Longjohn Anthony Erekosima; Ugodo Godwin; Cletus Amaduobogha (International Journal of Innovations in Engineering Research and Technology, 2022)
The efficiency of heat exchanger is dependent on the reliability and durability of its materials used at the design phase. The project is aimed at materials optimization and selection for the design of a shell and tube heat exchanger tube in order to mitigate failure mechanism such as erosion wear, fatigue and fouling resulting from fluid particles. Therefore, the need exists for high performance engineering materials and improved surface engineering application to mitigate the potential degradations due to erosion wear, fouling and fatigue. The material selection process was performed using the Cambridge Engineering Selector Edu-pack software Granta with limit and design constraints such as maximum service temperature 300, fracture toughness, elastic limit 120MPa. Materials such as MXT5 Copper composite, molybdenum alloy 363 TZM, molybdenum alloy 362 and tungsten metal (UNS no: R07004) are materials that satisfied the design requirement. The weighed property index method was further used to evaluate candidate materials based on the importance of the material properties. MXT5 Copper (5%) composite materials were finally proposed as the optimum material for the design of shell and tube heat exchanger tube because of its excellent mechanical properties such as high fracture toughness and impact strength, significant increase in thermal conductivity and low cost.